TRANSLATION QUALITY OF LITERARY TEXT OF INDONESIAN NOVEL “LASKAR PELANGI (THE RAINBOW TROOPS)” INTO ENGLISH USING FACEBOOK MACHINE TRANSLATION - Yeni Yulianti; Baharuddin; Lalu Jaswadi Putera; Udin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to identify and categorize the types of corrections or post-edits found in English translations of Indonesian literary texts and evaluate the quality of these translations using Facebook Machine Translation (FMT), specifically in translating the Indonesian novel "Laskar Pelangi" into English. Using a descriptive qualitative approach, the study examines various types of translation post-edits such as substitutions, insertions, deletions, and shifts, identified through HTER analysis. The correction or post-editing process for the English translation of the novel "Laskar Pelangi" using FMT was scrutinized and categorized by comparing the original Indonesian source text with the post-edited version translated by a professional human translator and by referring to the translated book version in English. The findings indicate that FMT achieves an 80.23% translation accuracy rating at the Good level based on TQI, with a 19.77% rate of translation inaccuracy. The types of post-edits identified include 54.2% substitutions, 33.7% insertions, 7.2% deletions, and 4.8% shifts. The analysis highlights a prevalent occurrence of substituted words in the post-edited translation, showcasing FMT's commendable performance in addressing translation issues on the popular platform.